Implementing the Flutter Educational Game "Bubble Math" to Improve Fifth Grade Students' Understanding of Arithmetic Operations - Lionza, Rahmat; Sidhiq Andriyanto; Tri Agusti Farma (KHARISMA Tech, 2026)
Mathematics learning in elementary schools generally still uses conventional methods, resulting in low student interest and understanding of arithmetic concepts. This research was conducted to develop an interactive learning medium in the form of an Android-based educational game called Bubble Math, designed for 5th-grade Public Madrasah Ibtidaiyah students. The game was developed using the Flutter framework. The game employs a drag and drop mechanic to train students’ accuracy and speed in solving basic arithmetic operations, including addition, subtraction, multiplication, and division. The development process followed the Game Development Life Cycle (GDLC) method, which consists of six stages: Initiation, Pre-production, Production, Testing (Alpha), Testing (Beta), and Release. The test results showed a 22.3% increase in Pretest-Posttest scores, with a User Acceptance Test (UAT) score of 91.09% from students. Therefore, Bubble Math is proven to be a feasible and effective medium for arithmetic learning in elementary schools.